POTASSIC PRIMARY MELTS OF VULSINI (ROMAN PROVINCE): EVIDENCE FROM MINERALOGY AND MELT INCLUSIONS - Kamenetsky V.; Métrich N.; Cioni R. (My University, 1995)
The origin and the relationships between the high potassic (HKS) and potassic (KS) suites of the Roman Comagmatic Province and the nature of their primary magmas have been intensively debated over the past 35 years. We have addressed these problems by a study of mineralogy (olivine Fo92-87, Cr-spinel and diopside) and melt inclusions in olivine phenocrysts from a scoria sample of Montefiascone (Vulsini area). This rock is considered as one of the most primitive (MgO=13.5 wt%, NiO=340 ppm; Cr=1275 ppm) in the northern part of the Roman Comagmatic Province. The compositions of both the olivine and their melt inclusions are controlled by two main processes. In the case of the olivine Fo92-90.5) and the Cr-spinel (Cr#=100. Cr/(Cr+Al)=63-73) represent a near-primary liquidus assemblage and indicate the mantle origin of their parental magmas. The compositions of melt inclusions in these olivine phenocrysts correspond to those of poorly fractionated H2O-rich ( 1 wt%) primary melts (MgO=8.4-9.7 wt%,FeOtotal=6-7.5 wt%). They evidence a wide compositional range (in wt%: SiO2=46.5-50, K2O=5.3-2.8, P2O5=0.4-0.2, S=0.26-0.12; Cl=0.05-0.03, and CaO/Al2O3= 0.8-1.15), with negative correlations between SiO2 and K2O, Al2O3 and CaO, as well as positive correlations between K2O, and P2O5, S, Cl, with nearly constant ratios between these elements. These results are discussed in terms of segregation of various mantle-derived melts. The high and constant Mg# [100.Mg/(Mg+Fe2+)] 73-75 of studied melts and their variable Si, K, P, Ca, Al, S contents could be explained by the melting of a refractory lithospheric mantle source, heterogeneously enriched in phlogopite and clinopyroxene (veined mantle source).